The Effect of Return on Asset, Non Debt Tax Shield, Asset Growth, Company Size, and Current Ratio, Against Debt to Asset Ratio on Companies Consumer Goods Listed on Indonesia Stock Exchange for the Period (2011-2017) - Susi Artati (Journal of Accounting and Finance Management, 2020)
This research was conducted on Consumer Goods companies listed on the IDX (Indonesia Stock Exchange) for the period 2011 - 2017, aiming to examine the effect of Return on Assets (ROA), Non debt tax shield (NDTS), Asset Growth (GROWTH) Company Size (Size) , and Current Ratio (CR) simultaneously or partially to Debt to Asset Ratio (DAR). The sampling technique used was purposive sampling. The sample used in this study amounted to 26 companies, a total of 182 data. The data analysis technique in this research is multiple linear regression analysis, classic assumption test (normality, multicollinearity, heteroscedasticity, and autocorrelation), hypothesis testing, and the coefficient of determination. The software used for data processing is SPSS 22.0. The results of multiple linear regression analysis show the equation Ln_DAR = 2.119 - 0.041Ln_ROA + 0.091 Ln_NDTS + 0.0003 Ln_GROWTH - 0.030 Ln_SIZE - 0.565 Ln_CR + e with an F test of 103.468. The t-test value for the Return on Assets (ROA) variable is -2.529; the t-test value for the Non debt tax shield (NDTS) variable was 2,629; t test value for asset growth variable (GROWTH) is -0.014. t test value for variable firm size (Size) is -0.172; Current Ratio (CR) variable t test value of -21,437. The coefficient of determination (Adjusted R Square) is 0.739 or 73.9%, while the remaining 26.1% is influenced by other factors outside of this research model.